2021
DOI: 10.1186/s13731-021-00174-4
|View full text |Cite
|
Sign up to set email alerts
|

Preferred leadership style, managerial and entrepreneurial inclination among Hungarian students

Abstract: Although a great deal of research has been done on leadership styles, and university students have often been the subject of exploratory research in social sciences, the Full Range Leadership model has been applied to young people only in a few instances. In this article, the authors seek to survey the preferred leadership styles among Hungarian students and explore how they correlate with managerial and entrepreneurial inclination. A complex analysis of leadership style preferences of university students comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The researchers used the positivist approach due to the frequent use of this powerful technique based on numerical facts. The procedure is known as a quantitative strategy that pursues consistencies in the human beings' social lives and systematically represents statistical facts (Payne and Payne, 2004). Moreover, in the field of entrepreneurship, various scholars, such as Singh (2000), Taormina and Lao (2007), Sandhu et al (2011), Noor and Isa (2020) and Zhu et al (2022), have applied this strategy to collect the quantitative facts from the respondents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers used the positivist approach due to the frequent use of this powerful technique based on numerical facts. The procedure is known as a quantitative strategy that pursues consistencies in the human beings' social lives and systematically represents statistical facts (Payne and Payne, 2004). Moreover, in the field of entrepreneurship, various scholars, such as Singh (2000), Taormina and Lao (2007), Sandhu et al (2011), Noor and Isa (2020) and Zhu et al (2022), have applied this strategy to collect the quantitative facts from the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Among Hungarian University students, transformational style is positively associated with EI. Moreover, entrepreneurial aspirations predict supportive leadership styles (Perp ek et al, 2021). On the one hand, in developing countries such as India, both male and female students are inclined to be entrepreneurs and want to start their own businesses.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Michalko (2001) showed that creativity was more likely to occur when leaders avoid letting their judgment emerge when a follower speaks. Various leadership theories have been described, including authoritative, coaching, and democratic ( Goleman, 2000 ; Al Harbi et al, 2019 ; Perpék et al, 2021 ). However, only a few have tested in R&D environments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Further work also emphasized that the supervisory style employed by the leaders toward creativity was positively related to performance ( Mednick and Mednick, 1967 ; Xenikou, 2017 ; Tong, 2020 ). Research has also shown that leaders play a significant role in exploiting the outcomes of R&D projects by triggering cooperation among teammates and communicating and sharing the body of knowledge and skills ( Gillespie and Mann, 2004 ; Carayannis et al, 2021 ; Perpék et al, 2021 ) efficiently. It has been proposed that the most influential leadership theories are the transformational and the transactional leadership theories ( Bass, 1985 ), which are related to innovation performance both at the individual and the team levels and when whole organizations are the unit of measurement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%